2015
DOI: 10.1038/ncomms7836
|View full text |Cite
|
Sign up to set email alerts
|

Logging cuts the functional importance of invertebrates in tropical rainforest

Abstract: Invertebrates are dominant species in primary tropical rainforests, where their abundance and diversity contributes to the functioning and resilience of these globally important ecosystems. However, more than one-third of tropical forests have been logged, with dramatic impacts on rainforest biodiversity that may disrupt key ecosystem processes. We find that the contribution of invertebrates to three ecosystem processes operating at three trophic levels (litter decomposition, seed predation and removal, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 48 publications
6
133
0
Order By: Relevance
“…Reductions in biodiversity are lower at lower logging intensities (48), under reduced-impact logging (49), and when areas of primary forest are spared within concessions (11). The contribution of invertebrates to litter decomposition, seed predation and removal, and invertebrate predation is reduced by up to one-half on Borneo, but increases in the abundance of small mammals, amphibians and insectivorous birds compensate to retain these ecosystem processes at primary forest levels (50). Forest heath is therefore maintained, but only if the forest is not further degraded or deforested ( Fig.…”
Section: Recent Changes In Forest Function and Healthmentioning
confidence: 99%
“…Reductions in biodiversity are lower at lower logging intensities (48), under reduced-impact logging (49), and when areas of primary forest are spared within concessions (11). The contribution of invertebrates to litter decomposition, seed predation and removal, and invertebrate predation is reduced by up to one-half on Borneo, but increases in the abundance of small mammals, amphibians and insectivorous birds compensate to retain these ecosystem processes at primary forest levels (50). Forest heath is therefore maintained, but only if the forest is not further degraded or deforested ( Fig.…”
Section: Recent Changes In Forest Function and Healthmentioning
confidence: 99%
“…Studies currently underway at the Biological Dynamics of Forest Fragments Project (BDFFP) in Brazil (Meyer et al, unpublished data) or at the Stability of Altered Forest Ecosystems (SAFE) Project in Borneo (e.g., Struebig et al 2013) provide examples of first efforts in this direction. The need for broader geographic coverage notwithstanding, directing more research to well-studied systems or long-term study sites, allows the responses of bats to land-use change to be compared to those of other taxa (e.g., Barlow et al 2007;Bicknell et al 2015;Ewers et al 2015). 4.…”
Section: General Conclusion and Future Research Directionsmentioning
confidence: 99%
“…In forest ecosystems, Ewers et al 10. showed that the contribution of insect and other invertebrate taxa to litter decomposition, seed predation and invertebrate predation was halved following logging because of a significant decrease in invertebrate abundance.…”
mentioning
confidence: 99%